2020
DOI: 10.20944/preprints202004.0015.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Screening of Molecules Approved in Phase-I Clinical Trials to Identify 3CL Protease Inhibitors to Treat COVID-19

Abstract: Ligand and structure based virtual screening approaches were applied to clinical stage drugs as well as those approved for human use in an attempt to repurpose drugs for potential use against COVID-19. This approach involved ligand-based shape similarity searches, structure-based docking and pharmacophore searches with the help of pharmacophore queries derived from available ligands and receptor structures. Several compounds appeared as hits in pharmacophore and shape similarity searches and those docking to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Currently, darunavir, lopinavir, and ritonavir are being used as a supportive medication against SARS-CoV-2 . Sahu et al performed molecular docking calculations to identify various protease inhibitors from a pool of 2827 molecules under clinical trials (Sahu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, darunavir, lopinavir, and ritonavir are being used as a supportive medication against SARS-CoV-2 . Sahu et al performed molecular docking calculations to identify various protease inhibitors from a pool of 2827 molecules under clinical trials (Sahu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that some of the drug moieties have better stability and binding a nity towards SARS-CoV-2 RdRp. Sahu et al 2020, have worked by taking SARS-CoV-2 3CL pro as a drug target in COVID-19 [10]. In our earlier attempts we found out that penicillin's had the potential to bind to M pro consistently, while phenoxymethylpenicillin and carbenicillin had high potential to act as an anti-COVID-19 agent which can be used alongside with anti-viral agents [11].…”
Section: Introductionmentioning
confidence: 90%